2022
DOI: 10.1051/e3sconf/202234800025
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Development of Beef Cattle, Sheep, Goat and Derivative Products through the Application of Digital Marketing in Facing the Impact of Covid-19 Pandemic

Abstract: Livestock business especially beef cattle, sheep and goat, experienced the marketing problems during the pandemic of Covid-19, which resulted a decrease in farmers income. Although there was a decline in purchasing power, data showed that during the pandemic, the demand of processed livestock products increased 3-4 times compared to before the outbreak of pandemic. This condition due to the changes in consumer preferences who wanted the product that have quality standards of health and food safety, and indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Among the main impacts experienced by the agricultural sector, disruptions and delays in breeding activities in both animal and plant production due to the quarantine and restrictions imposed have caused producers to remain below their optimum production levels and thus reduced the income obtained. In addition, difficulties in the marketing of agricultural products, the decline in people's purchasing power, and the reduced ability of households to access affordable food have also affected the economic resilience of farmers and breeders (Faturokhman et al, 2022). Within livestock breeding, especially cattle, sheep, and goat breeding, marketing problems were undergone during the COVID-19 outbreak, which led to decrease in farmers' incomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the main impacts experienced by the agricultural sector, disruptions and delays in breeding activities in both animal and plant production due to the quarantine and restrictions imposed have caused producers to remain below their optimum production levels and thus reduced the income obtained. In addition, difficulties in the marketing of agricultural products, the decline in people's purchasing power, and the reduced ability of households to access affordable food have also affected the economic resilience of farmers and breeders (Faturokhman et al, 2022). Within livestock breeding, especially cattle, sheep, and goat breeding, marketing problems were undergone during the COVID-19 outbreak, which led to decrease in farmers' incomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was a decrease in purchasing power, data showed that the demand for processed livestock products during the pandemic period increased 3-4 times compared to the pre-pandemic period. This is due to a shift in consumer preferences for products with health and food safety quality standards, which points to a great opportunity for increased sales of products for beef cattle, sheep, and goats (Faturokhman et al, 2022). Food supply is a linear system in which one stage is fed by the other.…”
Section: Introductionmentioning
confidence: 99%